2019
DOI: 10.3390/molecules24132466
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of 1-(3′,4′-Dihydroxyphenyl)-3-(2″,4″,6″-trihydroxyphenyl)-propan-2-ol from Grape Seed Extract and Evaluation of its Antioxidant and Antispasmodic Potential

Abstract: HPLC profiling of phenolics in grape seed extracts revealed a prominent peak of an unknown substance with concentrations up to 5.3%. Spectroscopic data allowed the identification of the compound 1 as 1-(3′,4′-dihydroxyphenyl)-3-(2″,4″,6″-trihydroxyphenyl)-propan-2-ol. 1 is known to be produced from catechin and epicatechin through anaerobic bacteria from human, as well as the rat, intestines. It was hypothesized that the marc remaining after expression of juice from grapes became infested during storage, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…Its molecular weight was also confirmed by UHPLC-MS analysis in positive and negative mode indicating protonated and deprotonated molecules at m / z 293 and 291, respectively. The product-ion spectrum for m / z 291 provided characteristic fragmentation ions at m / z 123, 247, 135 and 167, which is in agreement with previous reports [ 20 , 21 ]. The MS 2 fragmentation at 123.04 and 135.04 originated from the loss of C 8 H 9 O 4 and the combined loss of C 8 H 9 O 4 and H 2 O from the parent ion, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Its molecular weight was also confirmed by UHPLC-MS analysis in positive and negative mode indicating protonated and deprotonated molecules at m / z 293 and 291, respectively. The product-ion spectrum for m / z 291 provided characteristic fragmentation ions at m / z 123, 247, 135 and 167, which is in agreement with previous reports [ 20 , 21 ]. The MS 2 fragmentation at 123.04 and 135.04 originated from the loss of C 8 H 9 O 4 and the combined loss of C 8 H 9 O 4 and H 2 O from the parent ion, respectively.…”
Section: Resultssupporting
confidence: 92%
“…plantarum isolated from cheese, were found to cleave the heterocyclic ring of monomeric flavan-3-ols, giving rise to 1-(3′,4′-dihydroxyphenyl)-3-(2″,4″,6″-trihydroxyphenyl)propan-2-ol (3,4-diHPP-2-ol) [90]. This compound, which can be further degraded by the gut microbiota in several other substances, was recently studied for its antioxidant properties [91]. The authors found that 3,4-diHPP-2-ol had scavenging activity on ABTS and DPPH radicals higher than its precursor, as well as than other phenolic compounds.…”
Section: Effect Of Microbial Fermentation On the Antioxidant Activitymentioning
confidence: 99%
“…This result is consistent with those previously reported in the literature. 51 In the FRAP assay, the ferric ion reducing capacity of EGC′ was 1.50-fold that of EGC. However, EGC and EGC′ showed no significant difference in DPPH and ABTS assays.…”
Section: Chemical Antioxidant Activitymentioning
confidence: 96%